Development and Validation of an Egocentric Social Network Questionnaire for Parents of Children with Autism Spectrum Disorder - PAN Yuanyuan; LIU Qianqi; LIANG Minlu; WU Dandan; LIN Feng (康复学报, 2025)
ObjectiveAn egocentric social network questionnaire for parents of children with autism spectrum disorder(ASD) in China was preliminarily developed and tested for its reliability and validity, so as to facilitate the evaluation of parents' social networks and follow-up research.MethodsA convenience sample of 123 parents of children with ASD who visited the Department of Child Health at Children's Hospital of Nanjing Medical University, from August 2022 to March 2024 were selected as the study subjects. The general data questionnaire, egocentric social network questionnaire and perceived social support scale were used to conduct the survey. Trained rehabilitation therapists and psychotherapists guided parents filled out the questionnaires. The egocentric social network questionnaire was designed using nomination generation and nomination interpretation methods. The questionnaire first required parents to nominate people who supported them in raising their children, and then answer other questions related to the nominated persons, such as network size, interaction frequency, geographic distance, satisfaction level, and type of support. The questionnaire assigned weight values based on the social relationship distance between parents and the nominated persons and scored the answers. Cronbach's α coefficient and McDonald's ω coefficient were used to verify the reliability of the egocentric social network questionnaire. With perceived social support scale as the criterion, Pearson correlation analysis was used to evaluate the validity of the egocentric social network questionnaire.ResultsThe egocentric social network questionnaire for parents of children with ASD showed good reliability and validity. The Cronbach's α coefficient was 0.914 for the total score of the questionnaire, 0.937 for the network size, 0.861 for the interaction frequency, 0.886 for the geographic distance, 0.874 for the satisfaction level, and 0.895 for the type of support. The McDonald's ω coefficient for the total score of the questionnaire was 0.964. The Pearson correlation coefficients r values between the network size, interaction frequency, geographic distance, type of support, satisfaction level and total score of the questionnaire and the total score of the perceived social support scale were 0.51, 0.52, 0.49, 0.58, 0.49 and 0.56, all with P<0.001,indicating strong correlations.ConclusionThe egocentric social network questionnaire for parents of children with ASD has good reliability and validity. The questionnaire evaluation method is simple and time-saving, with good practicality and practicality, and can be used as an evaluation tool for the social network of parents of children with ASD in China. However, it is still necessary to expand the sample size and further improve the questionnaire for future research and application.